PENGARUH PENGAWASAN PROPAM TERHADAP PENINGKATAN KINERJA DAN DISIPLIN ANGGOTA POLRI: STUDI MANAJEMEN SDM - Marten Gunawan; Suharno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the influence of supervision by the Propam (Professional and Security) Division on the performance and discipline of members of the Indonesian National Police (Polri). Using a qualitative approach with descriptive-exploratory methods, this study aims to uncover how Propam's supervisory mechanisms influence the performance and discipline of Polri members from a human resource management perspective. Through in-depth interviews, participant observation, and document analysis, this study explores the meaning of supervision, Polri members' responses to supervision, and its implications for the formation of professional identity and behavior. The results reveal a complex pattern in the relationship between supervision and performance and discipline, mediated by the context of police organizational culture. This research generates theoretical propositions and practical recommendations for developing an adaptive supervisory approach in Polri human resource management.